The new Machiavelli how to wield power in the modern world - Powell, Jonathan (London Bodley Head, 2010)
In a 21st-century reworking of Niccol Ṃachiavelli's influential masterpiece, Jonathan Powell argues that the Italian philosopher is misunderstood, and explains how the lessons derived from his experience as an official in 15th-century Florence can still apply today. Drawing on his own unpublished diaries during his time as Blair's chief of staff, Powell gives a frank account of the intimate details of the internal political struggles, including the failure to join the Euro or hold a referendum on the European constitution; the wars in Iraq, Afghanistan, and Kosovo; the peace negotiations in Northern Ireland; and the relations with Clinton, Bush, and Chirac. Short, stark, and clear?much like The Prince?this gripping account of life inside "the bunker" of Number 10 draws lessons from those experiences, not just for political leaders but for anyone who has access to the levers of power.
Includes bibliographical references (p. 315-317) and index
Keywords: Blair, Tony, 1953-